Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

simplify the expression below. Express the simplified expression in standard form (12s^4-6s^2+4s)+(6s^4-4s+27)-(4s^4+s^2+12)

Sagot :

Answer:   14s^4 - 7s^2 + 15

====================================================

Work Shown:

(12s^4-6s^2+4s)+(6s^4-4s+27)-(4s^4+s^2+12)

12s^4-6s^2+4s+6s^4-4s+27-4s^4-s^2-12

(12s^4+6s^4-4s^4)+(-6s^2-s^2)+(4s-4s)+(27-12)

14s^4-7s^2+0s+15

14s^4-7s^2+15

Note: don't forget to distribute the negative to every term in the last parenthesis

Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.